The impact of the COVID 19 pandemic on European airlines' passenger satisfaction - Pereira, Francisco Costa (2021)
The COVID-19 pandemic brought many challenges to the airline industry, resulting in radical changes to the passengers’ experience. The purpose of this study is to understand the differences in customer satisfaction between the pre-COVID-19 period and during the COVID-19 pandemic, as well the factors that influence said satisfaction. The sample of this study consists of a dataset with 9,745 reviews written by passengers on the well-known airline reviews website, airlinequality.com, owned by SKYTRAX. The reviews were analyzed with a sentiment analysis tool that was specially calibrated for the aviation industry to be more accurate. The findings of this study show that passengers were unhappy with airlines before the pandemic, and those feelings were aggravated after the COVID-19 outbreak. The behavior of airline staff is the main factor to influence passengers’ satisfaction. The main takeaway is that passengers, after the pandemic, are mostly worried with refunds and aircraft cabin cleanliness. This study shows that analyzing passenger reviews is an effective way of gathering customer feedback, paving the way for airlines to continuously improve their service offerings.